The Role of E-Commerce and Mobile Applications in Empowering Push Cart Vendors at Jamshoro Phattak, Sindh, Pakistan - Syed Fateh Muhammad Shah; Shuja Ahmed Mahesar; Jawad Hussain Awan (Social Science Review Archives, 2025)
This research discovers the issues and possible solutions for push cart vendors working at Jamshoro Phattak, Sindh, Pakistan, a significant urban place wherever these vendors play a dynamic part in the local economy. Notwithstanding their support to providing reasonable properties and services, push cart vendors aspect several problems such as insufficient infrastructure, imperfect admission to economic resources, lawful barriers, and healthiness and security risks. The research highlights the part of e-commerce and mobile applications in dealing these issues, offering possible solutions to progress vendor processes, increase their market scope, and boost financial enclosure. By investigative these challenges and solutions, the research purposes to offer a route for sustainable development for push cart vendors, leveraging technology and supportive strategies.